Getting the Assumptions Right : Private Sector Participation Transaction Design and the Poor in Southwest Sri Lanka - van den Berg, Caroline; Pattanayak, Subhrendu; Yang, Jui-Chen; Gunatilake, Herath (World Bank, Washington, DC, 2014)
The need for reform in urban water and sanitation service delivery is urgent. Countries are making moves to achieve reforms, bringing in changes to the way they manage utilities, charge for water, and regulate the sector. This paper investigates how a set of basic assumptions on service coverage, service levels, tariffs, and subsidies in the proposed transactions in southwest Sri Lanka held up against consumer preferences. This paper provides the background information and describes the main features of the survey data. The paper then discusses a set of features that were used in the initial transaction design. This is followed by information on the impact of the different household preferences on these transaction features, and what this means in term of redesigning these features to ensure that the transaction would be more pro-poor. Conclusions and policy recommendations follow in the final section of this report.